Macroeconomic Costs of Higher Bank Capital and Liquidity Requirements - Roger, Scott; Vlcek, Jan. (Washington, D.C. : International Monetary Fund, 2011)
This paper uses a DSGE model with banks and financial frictions in credit markets to assess the medium-term macroeconomic costs of increasing capital and liquidity requirements. The analysis indicates that the macroeconomic costs of such measures are sensitive to the length of the implementation period as well as to the adjustment strategy used by banks, and the scope for monetary policy to respond to the regulatory changes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet